Characterization of dye Industry Effluent and Assessment of Its Suitability for Irrigation Purpose - Jolly, YN; Islam, A; Mustafa, AI (Journal of Bangladesh Academy of Sciences, 2009)
A study was carried out to characterize dye industry effluent by measuring its various physicochemical characteristics and trace heavy metals and to asses its quality to be used as an alternate means of irrigation. As a case study the results obtained from the investigation of effluent of the Bangladesh Dyeing and Finishing Industries Ltd., Karnapara, Savar are reported in this study. The direct effluent (untreated effluent) and after it was treated in the laboratory (treated effluent) were investigated. As groundwater is a part of the effluent, it was also analysed. The average pH values of the untreated and treated effluents were found to be 7.83 and 5.13, respectively. The EC values of the untreated effluent (1.81mS cm-1) and treated effluent (2.01 mS cm-1) were found to be higher than that of groundwater (0.93 mS cm-1). No significant variation in pH and EC values of monthly collected effluent samples was observed. The average concentrations of trace elements except Fe were found to be lower than their DoE recommended values for irrigation land. The concentrations of Na and K in the untreated effluent were found to be higher and the Ca and Mg concentrations lower than those of the treated effluents. Assessment of the untreated and treated effluent was made based on their EC, the sodium adsorption ratio (SAR) and soluble sodium percent (SSP), COD and heavy trace metal contents. From the overall assessment, the treated effluent was found to be suitable for irrigation. DOI: 10.3329/jbas.v33i1.2954 Journal of Bangladesh Academy of Sciences, Vol. 33, No. 1, 99-106, 2009